COVID-19: Perspectives for the management of dental care and education - Bruno César de Vasconcelos Gurgel; Samuel Batista Borges; Raul Elton Araújo Borges; Patrícia dos Santos Calderon (University of São Paulo, 2020)
Abstract The rapid and abrupt transmission pattern of the SARS-CoV-2 unleashed the current COVID-19 pandemic, as recognized by the World Health Organization in March 2020. Considering the high risk of transmission of the virus in dental environments and the specificities in clinical practice, COVID-19 posed immediate challenges for dental care and education. Due to the need to establish infection prevention and control guidance in dental health settings to enable a safe clinical practice, this review aims to list the challenges and perspectives in managing dental care in services and schools. This review employed materials collected from PubMed and the main guidelines and studies on the novel coronavirus to provide an overview of the clinical procedures and decisions made by health care personnel in dental offices and dental schools. We expect the COVID-19 scenario to promote significant changes in clinical practice and dental education; dentists should seek specific and particular regulations for dental practice established by their state or country. Biosafety checklists are strongly recommended for appointments at dental services and face-to-face activities in dental schools.